Effect of impactor mass on the response of knee joint during finite element simulations. (19th May 2011) - Soni, Anurag; Chawla, Anoop; Mukherjee, Sudipto; Malhotra, Rajesh
In our previous studies, we have observed that active muscles affect the response of the knee joint under impact. This paper investigates if the mass of the impactor affects our earlier observations. Therefore, simulations of lateral impact just below the knee have been performed using impactors of two different masses (i.e., the heavy and the light impactor). Two pre-impact conditions of a freely standing pedestrian, representing a cadaver and an unaware pedestrian have been simulated. Stretch-based reflexive action was included in the simulations for an unaware pedestrian. The results indicate that: the light impactor does not load the knee joint to the extent a car does in real-life car-pedestrian crashes; irrespective of the impactor mass, active muscle forces significantly alter the ligament strains.